Capillary viscous flow and melting dynamics: Coupled simulations for additive manufacturing applications - Blank, Michael; Nair, Prapanch; Pöschel, Thorsten (International Journal of Heat and Mass Transfer, 2019)
The rate of melting of a solid and the rate of deformation of the resulting melt due to capillary forces are comparable in additive manufacturing applications. This dynamic structural change of a melting solid is extremely challenging to study experimentally. Using meshless numerical simulations we show the influence of the flow of the melt on the heat transfer and resulting phase change. We introduce an accurate and robust Incompressible Smoothed Particle Hydrodynamics (ISPH) method to simulate melting of solids and the ensuing fluid-solid interaction. We present validations for the heat transfer across the free surface and the melting interface evolution, separately. We then present two applications for this coupled multiphysics simulation method — the study of rounding of an arbitrarily shaped particle during melting and the non-linear structural evolution of three spheres undergoing agglomeration. In both the studies we use realistic transport and thermal properties for the materials so as to demonstrate readiness of the method for solving engineering problems in additive manufacturing.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Additive manufacturing; Incompressible Smoothed Particle Hydrodynamics; Latent heat; Melting dynamics; Phase change

DEM Simulation of the Powder Application in Powder Bed Fusion - Angelidakis, Vasileios; Blank, Michael; Ribeiro Parteli, Eric Josef; Roy, Sudeshna; Schiochet Nasato, Daniel; Xiao, Hongyi; Pöschel, Thorsten (Progress in Powder Based Additive Manufacturing, 2025)
The packing behavior of powders is significantly influenced by various types of inter-particle attractive forces, including adhesion and non-bonded van der Waals forces [4, 7, 8, 19, 41, 43]. Alongside particle size and shape distributions, the inter-particle interactions, particularly frictional and adhesive forces, play a crucial role in determining the flow behavior and consequently the packing density of the powder layer. The impact of various types of attractive forces on the packing density of powders with different materials and particle size distributions remains largely unexplored and requires further investigation. Accurately comprehending these effects through experiments while considering specific particle size distributions and material properties poses significant challenges.
CRIS-Team Scopus Importer:2025-05-30

Modeling surface tension in Smoothed Particle Hydrodynamics using Young-Laplace pressure boundary condition - Blank, Michael; Nair, Prapanch; Pöschel, Thorsten (Computer Methods in Applied Mechanics and Engineering, 2023)
We introduce a surface tension model for Smoothed Particle Hydrodynamics (SPH) using a Young-Laplace pressure boundary condition. Our model does not rely on fitting parameters and can be applied to different variants of SPH. We demonstrate its robustness and accuracy by simulating several notoriously difficult three-dimensional free surface flow problems driven by surface tension.(c) 2023 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2023-03-03

Surface tension and wetting at free surfaces in smoothed particle hydrodynamics - Blank, Michael; Nair, Prapanch; Pöschel, Thorsten (Journal of Fluid Mechanics, 2024)
Surface tension and wetting are dominating physical effects in microscale and nanoscale flows. We present an efficient and reliable model of surface tension and equilibrium contact angles in smoothed particle hydrodynamics for free-surface problems. We demonstrate its robustness and accuracy by simulating several three-dimensional free-surface flow problems driven by interfacial tension.
CRIS-Team Scopus Importer:2024-05-31
Keywords: capillary flows; contact lines

Temperature Gradients as a Source of Balling and Humping in Laser Processing of Titanium - Blank, Michael; Pöschel, Thorsten (Springer Nature, 2024)
The spheroidization of the melt in laser melting processes deteriorates the mechanical properties of the welding seam or the manufactured part. This phenomenon is called humping or balling. To improve the reliability of the product quality a thorough understanding of the occurring physical phenomena is indispensable. By comparison of three-dimensional Smoothed Particle Hydrodynamics simulations of single-line laser tracks of titanium with experiments, we show that high-temperature gradients reduce the wetting forces which act at the three-phase contact line which in turn promotes the fragmentation of the cylindrical melt.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Balling; Humping; Laser processing; Smoothed particle hydrodynamic